Responses of the Northern Bering Sea and Southeastern Bering Sea Pelagic Ecosystems Following Record‐Breaking Low Winter Sea Ice. Issue 16 (29th August 2019) - Duffy‐Anderson, Janet T.; Stabeno, Phyllis; Andrews, Alexander G.; Cieciel, Kristin; Deary, Alison; Farley, Edward; Fugate, Corey; Harpold, Colleen; Heintz, Ronald; Kimmel, David; Kuletz, Kathy; Lamb, Jesse; et al.
Abstract: Bering Sea sea ice during winter 2017–2018 was the lowest ever recorded. Ecosystem effects of low ice have been observed in the southeastern Bering Sea, but never in the northern Bering Sea. Observations in both systems included weakened water column stratification, delayed spring bloom, and low abundances of large crustacean zooplankton. Summer Cold Pool presence was extremely limited. Young walleye pollock production and condition were similar to prior warm years, though catches of other pelagic forage fishes were low. Summer seabird die‐offs were observed in the northern Bering Sea, and to lesser extent in the southeastern Bering Sea, and reproductive success was poor at monitored colonies. Selected bottom‐up responses to lack of sea ice in the north were similar to those in the south, potentially providing environmental indicators to project ecosystem effects in a lesser studied system. Results offer a potential glimpse of the broader Bering Sea pelagic ecosystem under future low‐ice projections. Plain Language Summary: During the winter of 2017–2018, there was a lack of winter sea ice in the northern and southeastern Bering Sea. This was unprecedented, and its implications were unknown, especially for the northern Bering Sea. Ecosystem surveys showed that oceanic plants and animals at the base of the food web were delayed in their spring production and food quality was generally low. Abundances of young walleye pollock, a commercial species important to the global fish market, were average in 2018, but catches of other forage fishes were lower. Seabird die‐offs in the northern Bering Sea were extensive. If heat‐related ecosystem changes previously observed in the southeastern Bering Sea ecosystem are now happening in the northern Bering Sea, disruptions to food webs and increased die‐offs could occur if oceans continue to warm in the future. Key Points: Response of the southeastern Bering Sea to lack of sea ice has been documented, but lack of sea ice in the north (2017–2018) is unprecedented Selected bottom‐up cascading pelagic ecosystem responses to record‐low sea ice are similar in the NBS and SEBS, though other components of the ecosystem may respond differently The SEBS may be used as a model to inform understanding of effects in the pelagic NBS, especially with continued warm ecosystem conditions persisting through 2019